2002
DOI: 10.1097/00000658-200210000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Posttransplant Lymphoproliferative Disorders in Liver Transplantation

Abstract: While PTLD continues to pose problems in patients receiving liver transplants, improvements in patient survival have been observed over time. While it is too early to assess the impact of new advances in prophylaxis, diagnosis, and treatment, such approaches are based on an increased knowledge of the pathophysiology of PTLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
180
2
6

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 209 publications
(203 citation statements)
references
References 43 publications
15
180
2
6
Order By: Relevance
“…In agreement with our observation, two recent single-center studies similarly reported no effect of time to tumor development on patient survival (38,39). Several reports have suggested differences between the clinical and biological characteristics of lymphomas that develop early or late after transplantation.…”
Section: Lymphomas After Solid Organ Transplantationsupporting
confidence: 93%
“…In agreement with our observation, two recent single-center studies similarly reported no effect of time to tumor development on patient survival (38,39). Several reports have suggested differences between the clinical and biological characteristics of lymphomas that develop early or late after transplantation.…”
Section: Lymphomas After Solid Organ Transplantationsupporting
confidence: 93%
“…In literature, PTLD has been reported to occur months or years after transplantation. The experiences of multicenter clinical studies in the European transplant centers support the use of mTOR inhibitors in the management of PTLD following renal transplantation, with a reported PTLD incidence of 1%-10% in adults and 9.7% in children (19,25,26). In our study, 13 (6.3 %) of the 206 pediatric patients developed de novo malignancies post-transplantation, and the mean time to the occurrence of PTLD was 37.7±26.6 months.…”
Section: Discussionsupporting
confidence: 60%
“…EBV infection and immunosuppression therapy are the most important risk factors for PTLD. The incidence of PTLD depends on several factors: the age of the transplant recipient, duration of post-transplant immunosuppression or types of immunosuppressants used, and EBV infection (18,19). Reduction or cessation of immunosuppression is the most common initial approach for the development of PTLD.…”
Section: Discussionmentioning
confidence: 99%
“…In the previously reported study from the University of Pittsburgh of PTLD in 4000 patients who were followed for nearly 20 years, the rate of PTLD decreased with time, and the children had a higher incidence than the adults. 37 …”
Section: Ptld In Relation To the Age And Length Of Follow-upmentioning
confidence: 99%